PROFIL HISTOPATOLOGI KANKER KOLOREKTAL DI INSTALASI PATOLOGI ANATOMIK RSUP DR. SARDJITO YOGYAKARTA TAHUN 2013 - , CHRISTIE HAMDALI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Colorectal cancer is the most common malignancy in the digestive tract. This leads to colorectal cancer becoming the 3rd highest cause of death in the world. The reason for this high rate is because more than half of the patients are diagnosed at the end stage, where managements are difficult. Objective: The aim of this retrospective descriptive study is to learn the epidemiology of colorectal cancer, which hopefully will increase the qualities of the diagnosis and management of colorectal cancer, especially in Yogyakarta. Method and Material: The data for this study was taken from the Anatomical Pathology Instalation at RSUP Dr. Sardjito in 2013. Result and Conclusion: The study results were measured, there were 77 colorectal cancer patients, composed of 46 men and 31 women, most of the patients age ranges between 50-69 years old. Adenocarcinoma (78%) was the most common type of histopathology with moderate differentiation (58.3%) as the most common grade. The condition with the highest average age is MALT Lymphoma, at 67 years old. Resection (63.6%) is the more commonly used method for specimen collection for diagnosing colorectal cancer. Most of the patients were found with stadium B (75.7%) cancer stage. The conclusion of this study is that colorectal cancer is common found in men in 5th decade of life. The most common histopathologic type found is moderate differentiation adenocarcinoma with stadium B cancer stage.